THE INFLUENCE OF SUBTITLE FILM ON STUDENTS’ LISTENING MOTIVATION - Nur Zahrah Azizah; Muhammad Yaumi (ETERNAL (English, Teaching, Learning and Research Journal), 2018)
This paper is aimed to describe the influence of making subtitle film  on students’  listening motivation. The population of this research is the second semester students of English Education Department in academic year 2016/2017. The method used in this paper was a quantitative method with experimental research design.  In addition, the research data were collected by using questionnaire. The data were analyzed through  Likert scale and descriptive statistics. The result research shows that the mean  score  of  students’  pre-questionnaire  is 60.9  from the total score  1462  and the post  questionnaire  is  65.8 from the total score 1580. The result of analysis indicates that in teaching listening by making subtitle film can increase their listening motivation. It proved by t-test which is higher than t-table.. It also means that there are a significant influence of the use subtitle film  in increasing students’ motivation in listening.